Education for Sustainable Development in Chemistry Teacher Education - Aksela, Maija (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
This article looks at education of sustainable development and research in The Unit of Chemistry Teacher Education in the University of Helsinki. This article presents the unit’s strategy for sustainable development and examples on how it is carried out in education. In addition it is described, how with the help of design research, we are able to promote practical teaching of sustainable development. Finally, the skills that are central in promoting sustainable development are presented and as well how to support these skills in meaningful teaching of chemistry and in its evaluation.